Ruania rhizosphaerae sp. nov., a novel actinobacterium isolated from rhizosphere of Suaeda aralocaspica. Issue 9 (20th September 2021) - Lu, Wan-Ni; Xu, Yi-Zhuo; Xie, Yuan-Guo; Gao, Rui; Song, Jie-Qiong; Liu, Dan-Feng; Xiao, Min; Wang, Hong-Fei; Li, Qiu-Li; Li, Wen-Jun
Abstract : A Gram-stain-positive, non-motile and short rod-shaped actinobacterium, designated strain LNNU 22110 T, was isolated from the rhizosphere soil of the halophyte Suaeda aralocaspica (Bunge) Freitag and Schütze, which collected in Xinjiang, north-west China. Growth occurred at 10–45 °C, pH 6.0–10.0 and in the presence of 0–11 % NaCl (w/v). Based on the results of 16S rRNA gene sequence phylogenetic analyses, strain LNNU 22110 T belonged to the genus Ruania and had 97.5 and 95.5 % sequence similarity to Ruania alba KCTC 19413 T and Ruania albidiflava CGMCC 4.3142 T, respectively. The digital DNA–DNA hybridization relatedness values between strain LNNU 22110 T and R. alba KCTC 19413 T and R. albidiflava CGMCC 4.3142 T were 23.2 and 19.9 %, respectively. The highest average nucleotide identity value between strain LNNU 22110 T and its closest related strain ( R. alba KCTC 19413 T ) was 80.2 %, much lower than the species delineation threshold of 95–96 %. The genome of strain LNNU 22110 T was 4.4 Mb, with a genomic DNA G+C content of 68.4 mol%. The diagnostic diamino acids in the peptidoglycan layer of strain LNNU 22110 T were lysine, alanine, glycine, glutamic acid and aspartic acid. The predominant menaquinone was MK-8(H4 ). The major fatty acid (>10 %) was anteiso-C15 : 0 . The polar lipid profile of strain LNNU 22110 T included diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol, diacylated phosphatidyl dimannoside, one unidentified glycolipid and two unidentified phospholipids. According to the phenotypic, phylogenetic and chemotaxonomic results, strain LNNU 22110 T is considered to represent a novel species of the genus Ruania, for which the name Ruania rhizosphaerae sp. nov. is proposed. The type strain is LNNU 22110 T (=KCTC 39807 T =CGMCC 1.17105 T ).